The Resistance of Farmer Groups in Protected Forest Management - Isnaini Isnaini; Sarmida Rezkina (LPPM Universitas PGRI Sumatera Barat, 2019)
The use and utilization of forests by most people who live on the edge of the forest is something that has been done for generations. One of the forests managed by the community is Gunung Leco Forest in Nagari Desa Baru, Pasaman Regency. However, this utilization cannot be carried out continuously because of the changing status of the forest from community forest to protected forest. This study aims to describe the form of social movements of farmer groups on the determination of forests into protected forests. This study uses qualitative research, data collection is done by in-depth interviews, observation and study of documents. The results showed that the farmer groups are still processing forests into oil palm plantations. They made a defensive effort by uprooting protected forest crossings sign which is installed inthe forest, organizing the gardening period, cutting down the oil palm they had planted. To date no agreement has yet been reached to resolve this conflict.